Economic losses induced by Fasciola hepatica in cattle slaughtered in Chacuba slaughterhouse, Camagüey, Cuba - Palacios, Danays; Bertot, J. A.; Baltrao, Marcelo; Vázquez, A.; Ortíz, R. C.; Varona, Melissa (Cuban Journal of Agricultural Science, 2019)
To determine the existence of seasonal patterns for the economic losses induced by Fasciola hepatica in cattle slaughtered in Camagüey province, Cuba, the monthly records of the 13,059 cattle slaughters were used, carried out in Chacuba slaughterhouse from the Unidad Empresarial Básica Comercializadora ganadera de Terso, belonging to Maraguán Cattle Enterprise. During the period between January 2008 and December 2014, a total of 2 387 animals affected by F. hepatica were used, a result of the anatomo-pathological diagnosis carried out in the slaughterhouse. From the slaughtered and affected animals, the losses for the whole period were calculated, with a value of 6,524.90 Cuban convertible pesos. The process of seasonal decomposition with an additive model showed, for the first time in Camagüey, the existence of seasonal performance for economic losses by F. hepatica. The seasonal pattern was characterized by peaks in February, October and December. It is recommended to evaluate the dynamics of intermediate hosts and larval stages of F. hepatica to relate them with seasonal patterns, observed for the economic losses caused by liver discards. Key words: seasonal, Fasciola hepatica, cattle, economic losses